(untitled) (Research, Society and Development, 2020)
It is acknowledged that mechanical damage is a major cause of post-harvest losses of potato tubers and the curing is an indispensable process to increase resistance to excoriation. Furthermore, the use of lower curing temperatures is required to maintain the quality and prolong the durability of the tubers. However, they may not allow adequate regeneration of the damage periderm, besides this effect being variable among genotypes. The present study evaluates histological outcomes in the periderm derived from the mechanical damage through a simulation of excoriation, as it is the most common during the harvest and post-harvest stages. Therefore, the objective of this study was to determine the effect of reducing the curing temperature on the number of layers and on the thickness of the damage periderm of potato tubers of cv. Innovator. Histometric analysis of the cork, phellogen, phelloderm and the total periderm of tuber, was performed using the Image-Pro Plus software (MediaCybernetics) after curing for 15 days. The number of layers and thickness of each periderm structural layers were determined from six measurements for each repetition. After curing, there was no formation of the cork and phelloderm in the tubers conducted at 8 ° C under the excoriation treatment, while all components of the periderm were formed at 14 and 20 °C. At 8 and 14 °C, the phellogen differentiated similarly in tubers conducted at control and mechanical damage treatments, while at 20 °C the thickness did not differ in any component of the periderm. The phellogen at 14 and 20 °C did not differ in the number of layers and thickness. The visual aspect of the tuber injuries at 14 and 20 °C emphasizing the regeneration. It is concluded that the reduction of the curing temperature to 8 °C provided slower cell regeneration. However, it is possible to conduct the curing procedure at 14 °C, without compromising the formation of the damage periderm. The cultivar Innovator has rapid cell regeneration at higher curing temperatures, therefore it is recommended that the tubers of this cultivar be cured at 14 or 20 ° C. The study evaluates the mechanical damage through a simulation of the damage by excoriation. The however, for a better understanding of the formation of the damage periderm, it is interesting that other studies evaluate different types of damage, such as impact, comprehension and abrasion, in order to assess the regeneration capacity according to the damage of this cultivar.